Return to Sport after Injury: A Web-Based Survey of Owners and Handlers of Agility Dogs - Tomlinson, Julia E.; Manfredi, Jane M. (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objective Internet-based surveys of canine agility injury rates have been performed, but unlike with equine and human competition, there is a paucity of data on return to sport of agility dogs after orthopaedic injury. This study aimed to gather initial information on canine return to competition.Methods Data were collected using an internet-based 18-question survey of 427 dogs from around the world (92.4% North America). Relationships between categorical variables and return to sport were assessed with descriptive statistics, a chi-squared or Fischer's exact test. Categorical variables included breed, sex, age, surgery, stifle versus shoulder surgery, stifle versus all other types of surgery and drop in competition class. Significance was set at p≤ 0.05.Results Of 427 completed surveys, age, sex and breed were not significantly associated with return to competition. Overall, 67.4% of dogs returned to competition post-orthopaedic injury, but jump height was lowered in 47% of cases. Dogs were returned to competition post-stifle surgery, but were the least likely of all injury types to return to competition (p = 0.044) and were more likely to compete at a lower class (p = 0.026).Clinical Significance While over half of all dogs returned to competition, just under half of that group decreased jump class. Dogs that have undergone stifle surgery have the worst prognosis for return to agility and if they return, they are more likely to drop class.
Keywords: sports medicine; dog; agility; shoulder; stifle